Information retrieved from specimens at Natural History Collections can improve the quality of field-based ecological networks - González Vaquero, Rocío Ana (2014)
Numerous studies analyze the interactions between plants and their pollinators in ecological communities using a network approach. However, field studies rarely record all the interactions occurring in the field. In this sense Natural History Collections (NHCs) can provide information on interactions that may have been missed by field sampling. In this study we compare a network based on field sampling with a network based on data retrieved from specimens at NHCs, and we assess the degree to which these two sources of data are complementary. For this we used data available from a bee biodiversity study conducted in Southern Argentina for the South American bee genus Corynura (Halictidae: Augochlorini). Data on the floral associations of the specimens at NHCs were retrieved from the specimens’ labels, as the name of the plant species on which a given bee was captured is often recorded for many specimens at NHCs. Although field sampling recorded an unusually high number of insect-plant interactions, it misses some unique interactions present in the NHCs networks. Some structural properties of these networks are briefly analyzed, and usefulness and limitations of using NHCs data are discussed. We conclude that the information about insect-plant interactions extracted from NHCs could complement field-based data, especially in poorly sampled communities.